FAKTOR-FAKTOR KEJADIAN KARIES GIGI PADA BALITA DI WILAYAH KERJA PUSKESMAS BETUNGAN KOTA BENGKULU - Katli, Katli (Journal of Nursing and Public Health, 2018)
The main problem of oral health of children is dental caries. Caries is a dental health problem incidence which is increasing. Factors that cause dental caries among gender, consumption of cariogenic foods/sweet, brushing teeth, dental care doctor. This study was conducted to determine the factors associated with the incidence of dental caries on toddlers in the region of Betunganhealth center. This study was an analytical study using case control design. The study population were all toddlers who came to visit the health center for dental treatment, with the sample size of 96 people, and the sampling technique used an accidental sampling. Data collection was done by direct interview using a questionnaire. Data was analyzed using univariate and bivariate analysis with chi-square test at Î± 5%. The results showed that most respondents (51.0%) frequently consume cariogenic foods, most respondents (55.2%) did not brush their teeth well, most respondents (58.3%) carried out dental care to the doctor was not effective, almost half respondents (47.9%) were female sex, and half of the respondents (50.0%) experienced dental caries. There was a relationship between the consumption of foods cariogenic, brushing and dental care to the doctor with the incidence of dental caries in BetunganHealth Center in Bengkulu(Ï = 0.000), and there was no relationship between gender and the incidence of dental caries in Betunganhealth center in the city of Bengkulu (Ï = 0.540). It is expected that health workers in the health center of Betungan can be a channel of information and give more intensive counseling and health promotion of the factors associated with the incidence of dental caries, as well as convey the prevention of dental caries.